MENINGKATKAN KINERJA BUNDARAN KELAPA GADING DENGAN SIMPANG BERSINYAL MENGGUNAKAN SOFTWARE PTV VISSIM STUDENT VERSION - Setiono, Bagus; Putra, Fisika Prasetyo; Abriantoro, Adji Putra (Universitas 17 Agustus 1945 Jakarta, 2021)
The Kelapa Gading roundabout junction, North Jakarta is one of the unsignalized intersections with the roundabout. Traffic conditions that have a density in every arm, trigger traffic jams during rush hours. In this study, an analysis of the performance of the Kelapa Gading roundabout will be presented.Primary data includes geometric, environmental conditions, traffic flow and location maps. While secondary data includes population and vehicle growth in DKI Jakarta Province. The research method uses the formula contained in the 1997 MKJI and modeling using the Vissim Student Version softwareAfter evaluating the average roundabout performance, it was found that DS < 0.69, capacity of 7927 pcu/hour, intersection current 5286 emp/hour at the average intersection at the peak hour of the roundabout, in this case the roundabout is still feasible to maintain. However, in this study, forecasting in the next 5 years was obtained in the 3rd year (three) the degree of saturation reached DS > 0.75 on one or several parts of the road so it could change to a signalized intersection, in this study we will use the PTV Vissim Stundent Version software to perform analysis of existing conditions and plans. Key words: Signalized intersection, MKJI, vissim.